Subject Matter : Contemporary Painting and Sculpture in Nova Scotia. - Metcalfe, Robin; Riordan, Bernard; Metcalfe, Robin (Halifax : Art Gallery of Nova Scotia, 1992)
Atkin, David ; Callaway, Malcolm ; Crichton, Susan Tooke ; Cropas, Nyna ; Delva, Thierry ; Edell, Nancy ; Gauthier, Suzanne ; Gill, Dennis ; Greer, John ; Haigh, David ; Hamm, Harry ; Livingston, Alex ; MacPhee, Teresa ; McAvoy, Marilyn ; Mueller, Richard ; Zimmerman, Carl
biografie, bibliografie
Subject Matter : Contemporary Painting and Sculpture in Nova Scotia, Art Gallery of Nova Scotia, Halifax, 2 May to 12 July 1992
Engels
boek